Does being on TB treatment predict a higher burden of problems and concerns among HIV outpatients in Kenya? a cross-sectional self-report study. (20th June 2018) - Nkhoma, Kennedy; Ahmed, Aabid; Ali, Zipporah; Gikaara, Nancy; Sherr, Lorraine; Harding, Richard
ABSTRACT: Tuberculosis illness is associated with uncertain outcomes, and has high prevalence among people living with HIV. The new World Health Organization's End TB strategy specifies person-centred symptom management and psychosocial support alongside treatment within its pillars and components. There is a paucity of research to inform an effective care response in Kenya in terms of self-reported outcomes. We aimed to measure the three day period intensity of problems and concerns (physical, psychological, social and spiritual), and identify predictors of problems and concerns, among HIV patients attending outpatient care. We conducted a cross-sectional self-report quantitative study among adult (aged at least 18 years) patients with confirmed HIV diagnosis, and aware of their diagnosis and attending HIV outpatient care in Kenya. Multi-dimensional palliative care problems and concerns were collected using African Palliative Outcome Scale (APOS). Ordinal logistic regression assessed the association of multi-dimensional problems and concerns controlling for demographic variables (age, gender, education and wealth) and clinical variables (WHO clinical stage, HIV treatment status, TB treatment status, and CD4 count). We recruited N = 400 participants. N = 61 (15.64%) were on TB treatment. The items with worst score responses were help and advice to plan for the future (52.5%), ability to share feelings (46.25%), at peace (30.75%) pain (27%) and life worthwhile (18.75%). TB treatment status was associated with lower (worse) score for APOS total score (odds ratio .59, 95% CI .36 to .99; P = 0.046) and factor 3(existential and spiritual wellbeing: .55, .32 to .92; p = 0.023). Interestingly higher CD4 count was predictive of lower (worse) factor 3 outcomes (existential and spiritual wellbeing: .84, 95% CI 73 to .97; p = 0.014). This study informs the new WHO End TB policy with novel data on specific clinical needs. This calls for holistic symptom assessment, person-centred care and holistic management to respond positively to the End TB strategy.